ANALISA PEMELIHARAAN KOREKTIF PADA ALAT PATIENT MONITOR DI RUMAH SAKIT UNIVERSITAS SUMATERA UTARA - Dody Wahyudi; Hotromasari Dabukke; Salomo Sijabat (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2024)
Patient monitor is a tool that functions to monitor the physiological condition of patients. Where the monitoring process is carried out in real-time. The purpose of this analysis is to find out how this corrective maintenance is carried out starting from the beginning to the end of the process. With this research, the author will get valid data about patient monitor tools, this research is also carried out in accordance with the rules of the law so that no violations will be created. The reason for using this patient monitor is so that things do not happen that can make the patient's condition worse and also medical technicians can find out the patient's condition in real time, in other words this patient monitor tool is made to assess the current condition of the patient and evaluate the influence of the patient's intervention. This monitoring tool can measure vital signs in patients, such as temperature, blood pressure, respiration, pulse rate which are displayed directly on the patient monitor screen itself in real time Corrective maintenance analysis on this patient monitor is equipped with a calibration tool that can help carry out this activity.